Outcome evaluation of a health promoting school approach intervention : an impact analysis of mental health outcomes among high school learners in the Capricorn District, Limpopo Province - Langa, Raisibe Cynthia (My University, 2020)
This thesis is an evaluation of a study that focused on the health promotion of learners in schools. The study evaluated the process of health promotion in the schools focusing on the school’s compliance as health-promoting schools in line with the WHO principles, the intervention process that includes training of students in health promotion and assessing the impact of such intervention. The intervention was delivered by Life Orientation (LO) Educators over nine months. The thesis aimed to evaluate if learners who have been exposed to the health-promoting school programmes will exhibit more confidence in avoiding and refusing to indulge in mental health-related risky behaviours than those who were not exposed; and whether the WHO health-promoting school approach compliance can be modified to establish site specific agenda regarding mental health. Twenty schools in two circuits within Capricorn district in Limpopo province participated in the evaluation process using eighteen schools that took part in the whole school intervention project of LASH project. Data was collected for process evaluation and impact analysis of the intervention. Process evaluation used data collected from the interview reports of LO Educators who implemented the project at schools and thus evaluated the process of their experience with the project. The impact analysis was done using data collected from the participants at baseline and a follow-up after nine months using a self-administered questionnaire. The process evaluation findings showed that the degree of understanding of the expected implementation objectives was not standardised and was not done according to the initial plan as well as following the contextual needs. Factors that came out explicitly as hindering the desired effect included neglect of key methodological aspects meant to enhance and validate the experiential report by the Educators namely classroom observation and logbook reports; specialisation of the topics for the intervention and lack of training manuals specific for the task; lack of adequate capacity building for staff, the schools to take charge of the process and neglect of the needs to avoid challenges for contextualrelevance. However, it is worth noting that the introduction of the process was done under the systematic recommendation by WHO with the schools adhering to the basic principles for health promotion outlined by WHO. The impact analysis evaluation highlighted some negative and positive results ofthe study. Positive results on the impact of the intervention elicited factors such as the development of learners’ assertiveness, learners’ utilisation of available policies in the school for their daily activities and change in risky behaviour. The gaps noted above were in the region of methodological aspects, capacity building, context-related challenges and recommendations were made in the areas of (i) enhancement of methodological gaps that were neglected in the main study; this included the utilisation of logbooks and classroom observation that were planned and did not materialise as well as more succinct validation of some items in the questionnaires that seemed to have created ambiguity in some responses ii) development of specific training manual for health promotion and not use of ad-hoc topics separately developed with limited capacity for comparability between schools iii) capacity building of staff to take full charge and act as role models for the learners and not feel compromised; iv) capacitation of the school management to assist with the daily logistics and enhancement for implementation especially at school level v) planning process that contextualise the needs of the schools involved. The project was ground-breaking work of whole school health promotion with promise in the behaviour changes of learners and their empowerment and aggressive outlook on the difficult school based challenges around substance abuse, violence and sexual behaviour. Such work could in future benefit from studies that are both theory and evidence-based which will use validated and contextualised realistic methods guided by the findings of pilot studies which was missing in this project.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2020
Keywords: Education; Health promotion; Life orientation; School; Mental health; Children mental health